Digital platforms and narrative exchange: Hidden constraints, emerging agency. (June 2015) - Clark, Wilma; Couldry, Nick; MacDonald, Richard; Stephansen, Hilde C
It is well known that narrative exchange takes distinctive forms in the digital age. Less understood are the digitally based processes and infrastructures that support or constrain the wider exchange of narrative materials. This article reports on research in a UK sixth form college with ambitions to expand its students' digital skills. Our approach was to identify the preconditions (sometimes, but often not, involving fully formed narrative agency) that might support sustained narrative exchange. We call these conditions collectively 'proto-agency', and explore them as a way of establishing what a 'digital story circle ' (not just a digital story) might be: that is, how new digital platforms and resources contribute to the infrastructures for narrative exchange and wider empowerment in a complex institutional context. During our fieldwork, interesting insights into the tensions around social media emerged. Only by understanding such forms of proto-agency can we begin to assess the participatory potential of digital platforms for young people in education today.